Predicting Next Label Quality: A Time-Series Model of Crowdwork - Jung, Hyun; Park, Yubin; Lease, Matthew (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
While temporal behavioral patterns can be discerned to underlie real crowd work, prior studies have typically modeled worker performance under a simplified i.i.d. assumption. To better model such temporal worker behavior, we propose a time-series label prediction model for crowd work. This latent variable model captures and summarizes past worker behavior, enabling us to better predict the quality of each worker’s next label. Given inherent uncertainty in prediction, we also investigate a decision reject option to balance the tradeoff between prediction accuracy vs. coverage. Results show our model improves accuracy of both label prediction on real crowd worker data, as well as data quality overall.